Pengaruh Kinerja Lingkungan, Profitabilitas, Ukuran Perusahaan dan Kepemilikan Saham Publik Terhadap Pengungkapan CSR di Bursa Efek Indonesia - Metri Metri; Solikah Nurwati; Rita Sarlawa (Fakultas Ekonomi Dan Bisnis Universitas Palangka Raya (UPR), 2021)
Research in the field of finance related to corporate social responsibility is an interesting topic in increasing the CSR disclosure of manufacturing companies. The influence of the importance of policies and actions Environmental performance, profitability, company size and public ownership can increase the disclosure of CSR responsibility for manufacturing companies on the IDX in 2015-2018. This research is related to the manufacturing industry because it has the largest number of companies than other types of industries that are sensitive to the general public and the influence of company stakeholder trust. The results show that it is very important for manufacturing companies to support CSR by environmental performance, profitability, company size and joint public ownership. The results in this study indicate that the disclosure of CSR in manufacturing companies listed on the IDX in 2015-2018 requires an antecedent for the greater the size of the antecedent, the more extensive the CSR disclosure that will be carried out. This confirms the agency theory of research which explains that the bigger a company is, the greater its CSR costs. But the results show that the profitability is not significant in increasing endogenous. So that further research includes financial literacy variables to increase the CSR of manufacturing companies. Practical research implications for stakeholders who get the good news that the company's CSR will increase the height of the work relationship, therefore it is very important for companies to expand and increase CSR for the sustainability of manufacturing companies